Christian Hebraism in the Reformation Era (1500-1660) : Authors, Books, and the Transmission of Jewish Learning. - Burnett, Stephen G. (Library of the written word., 2012)
The Reformation transformed Christian Hebraism from the pursuit of a few into an academic discipline. This book explains that transformation by focusing on how authors, printers, booksellers, and censors created a public discussion of Hebrew and Jewish texts.